2018
DOI: 10.1111/mpp.12684
|View full text |Cite
|
Sign up to set email alerts
|

The pepper Bs4C proteins are localized to the endoplasmic reticulum (ER) membrane and confer disease resistance to bacterial blight in transgenic rice

Abstract: Transcription activator-like effector (TALE)-dependent dominant disease resistance (R) genes in plants, also referred to as executor R genes, are induced on infection by phytopathogenic bacteria of the genus Xanthomonas harbouring the corresponding TALE genes. Unlike the traditional R proteins, the executor R proteins do not determine the resistance specificity and may function broadly in different plant species. The executor R gene Bs4C-R in the resistant genotype PI 235047 of the pepper species Capsicum pube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Also, bs5 has been mapped and its linked markers are available [18]. These five dominant loci (Bs1-Bs4, Bs7) have been shown to confer resistance to Xcv in a gene-forgene manner [5,7,[13][14][15][16][17]19]. The executor R gene Bs1 in the resistant genotype VI037601 of the pepper species Capsicum annum L. confers disease resistance to Xcv strain 23-1 harbouring the avirulence gene avrBs1 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, bs5 has been mapped and its linked markers are available [18]. These five dominant loci (Bs1-Bs4, Bs7) have been shown to confer resistance to Xcv in a gene-forgene manner [5,7,[13][14][15][16][17]19]. The executor R gene Bs1 in the resistant genotype VI037601 of the pepper species Capsicum annum L. confers disease resistance to Xcv strain 23-1 harbouring the avirulence gene avrBs1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, five non-allelic dominant hypersensitive resistance genes, Bs1 - Bs4 , Bs7 and two recessive non-hypersensitive resistance genes, bs5 and bs6 , have been used in pepper [ 7 , 12 , 13 ]. While Bs2 , Bs3 , Bs4 and Bs7 have been cloned, for their molecular markers for marker-assisted selection (MAS) were developed [ 5 , 14 17 ]. Also, bs5 has been mapped and its linked markers are available [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For bacterial pathogens expressing transcription activator-like (TAL) effectors that activate the expression of susceptibility genes in the host, resistance can be engineered by deletion of the TAL DNA binding sites in the promoter (Li et al, 2012;Jia et al, 2017). Another approach to engineer resistance to these bacterial pathogens is to add TAL effector binding sites to a cell-death-promoting ('executor') gene that is triggered by the TAL effectors present in common pathotypes (Hummel et al, 2012;Wang et al, 2018a).…”
Section: Intervention Based On Pathogen Recognition and Effectorsmentioning
confidence: 99%
“…In plants, the hypersensitive response (HR) is a form of programmed cell death (PCD) at the site of pathogen infection, which is closely related to active resistance [42]. Previous studies showed that Bs2, Bs3 and Bs4 were only expressed in BS resistant pepper post Xcv inoculation, which could trigger HR [15,16]. Here, transcriptome profiling analysis results showed that bs2 (Capana09g000438) and bs3 (Capana02g001306) were not/hardly expressed in pepper leaves before and after Xcv inoculation.…”
Section: Rna-seq Technique Was Adapted To Identify the Degs Associatementioning
confidence: 99%
“…To develop BS resistant commercially valuable cultivars through molecular breeding, four non-allelic hypersensitivity resistance genes, Bs1-Bs4, and two recessive non-hypersensitive resistance genes, Bs5 and Bs6, have been identified in pepper over the years [8,12]. Bs2, Bs3 and Bs4 are cloned, Bs2 and Bs3 develop molecular markers for marker-assisted selection (MAS) [5,[13][14][15][16]. Bs5 is positioned and its linked marker is also obtained [12].…”
Section: Introductionmentioning
confidence: 99%